1996
DOI: 10.1007/bf01466625
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound for diagnosis of apophyseal injuries

Abstract: Avulsion injuries of the apophysis is a problem in young athletes. A correct diagnosis is necessary for establishing the appropriate treatment and the rehabilitation program. However, it is often difficult to distinguish between a simple muscle strain and an avulsion fracture. The X-ray examination is helpful only when an ossification center of the apophysis exists. Ultrasonography is considered the suitable diagnostic tool for these cases. From June 1988 to June 1993, 243 young athletes were seen with an anam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 7 publications
1
30
0
2
Order By: Relevance
“…There is an opinion that during adolescence, the skeleton is more vulnerable than the tendons and muscles [7,8]. Frequency and/or excessive load to the growing skeleton can result in an SRBI and pain as symptoms [5].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an opinion that during adolescence, the skeleton is more vulnerable than the tendons and muscles [7,8]. Frequency and/or excessive load to the growing skeleton can result in an SRBI and pain as symptoms [5].…”
Section: Discussionmentioning
confidence: 99%
“…Frequency and/or excessive load to the growing skeleton can result in an SRBI and pain as symptoms [5]. Stress reactions or stress fractures in the enthesis in the pelvic girdle skeleton can therefore indicate the site of the pelvic pain [5,7,8,9,10]. This stress reaction or stress fracture has a better tendency to heal if recognized early [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Color-coded duplex ultrasound or power Doppler ultrasound may be helpful in distinguishing symptomatic from noninflamed lesions. General Considerations Ultrasound evaluation of musculosceletal injuries represents an ideal supplementary investigation to radiography in children [37][38][39]. Many musculoskeletal injuries and disorders can be visualized using high-resolution sonography (Table 1).…”
Section: Miscellaneousmentioning
confidence: 99%
“…Lazovic et al [2] reported that out of 234 suspected apophyseal fractures in adolescents, 80 were detected by radiography and 97 by ultrasound. Rathfelder and Paar [3] described good results in the first substantial study on the possible application of ultrasound in the diagnosis of fractures in children.…”
Section: Introductionmentioning
confidence: 98%